2019
DOI: 10.3389/fneur.2019.01175
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Val66Met Genetic Polymorphism Results in Poor Recovery Following Repeated Mild Traumatic Brain Injury in a Mouse Model and Treatment With AAV-BDNF Improves Outcomes

Abstract: Clinicians have long noticed that some Traumatic Brain Injury (TBI) patients have worse symptoms and take a longer time to recover than others, for reasons unexplained by known factors. Identifying what makes some individuals more susceptible is critical to understanding the underlying mechanisms through which TBI causes deleterious effects. We have sought to determine the effect of a single nucleotide polymorphism (SNP) in Brain-derived neurotrophic factor (BDNF) at amino acid 66 (rs6265) on recovery after TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 103 publications
(140 reference statements)
1
26
0
Order By: Relevance
“…It is known that BDNF signaling plays an important role in recovery after injury 38,95 . We have previously shown that treatment with overexpression of BDNF in susceptible BDNF Val66Met mice was able to improve outcomes after rmTBI 39 . This suggests that BDNF may be a potential therapeutic target for APOE4 carriers.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It is known that BDNF signaling plays an important role in recovery after injury 38,95 . We have previously shown that treatment with overexpression of BDNF in susceptible BDNF Val66Met mice was able to improve outcomes after rmTBI 39 . This suggests that BDNF may be a potential therapeutic target for APOE4 carriers.…”
Section: Discussionmentioning
confidence: 98%
“…Immunohistochemistry. To collect tissue for immunohistochemistry, after MRI scans, mice from the first cohort were perfused with 0.9% saline, followed by 4% paraformaldehyde at 1 or 21 days after the final injury as described previously 39 . After perfusion, the brains were cryoprotected with 30% sucrose for at least 3 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mutation of G to A results in an amino acid residue shift from valine (Val) to methionine (Met) at codon 66 within the BDNF prodomain, which interferes with a sortilin‐binding site disrupting in the intracellular trafficking and thus affecting the sorting of BDNF into secretory vesicles, resulting in reduction of activity‐dependent secretion (Notaras & Buuse, 2015). The rs6265 polymorphism has been found to be associated with memory performance (Kambeitz et al., 2012), Alzheimer disease (Huang, Huang, Cathcart, Smith, & Poduslo, 2007), Parkinson's disease (D'Souza & Rajkumar, 2019), traumatic brain injury (Giarratana, Teng, & Reddi, 2019), greater severity of CAD and incidence of CVD‐related clinical events (Jiang, Babyak, & Brummett, 2017), acute ischemic stroke (Zhou, Ma, & Fang, 2019), bipolar disorder (Lee, Wang, & Chen, 2016), major depression (Schumacher, Jamra, & Becker, 2005), and schizophrenia (Notaras & Buuse, 2015).…”
Section: Introductionmentioning
confidence: 99%